PENGGUNAAN EKSTRAK BUAH BITUNG DALAM PENGENDALIAN HAMA KEONG MAS (Pomacea caniculata L.) PADA TANAMAN PADI SAWAH (Oryza sativa L.) - Devita Gabai; Dantje Tarore; Reity A.G. Engka; Ronny Nangoi (COCOS, 2020)
ABSTRACT This study aims to determine the ef ect of beetroot ectract on the motality of Mas Keong (Pomacea caniculata L.) pests in Paddy Rice (Oryza sativa L.) which was carried out at the Green House of pests and Plant Diseases, Faculty of Agriculture Unsrat. The implementation time of this research was for three months from January 2020 to March 2020 and observations were made 1 day after application, 4 observations were made with a time interval of 6 hours. This study used a completely randomized design method with 5 treatments and 3 replications. Each replication consisted of 20 individual golden snails, so the total number of golden snails used was 300 individuals. The results of the research on the mortality observation of the mas snail pest showed that the mucus was released from the body of the golden snail so that the golden snail was poisoned due to the application of the extract of beetroot. Of the five treatments showed the percentage of snail pest mortality. The application of bitung fruit extract is Control = 0.00%, Extract Concentration 2% = 70.00%, Extract Concentration 4% = 80.00%, Extract Concentration 6% = 83.33% and Extract Concentration 8% = 100.00 %. <30 minutes the golden snail has stopped eating and its movements begin to slow down and burrow into the ground, over time its body will be released from its shell, this shows that the golden snail has died. Keywords : B. asiatica, P. caniculata, rice